ANALISIS KEBUTUHAN INFORMASI ORANG TUA TENTANG PENDIDIKAN ANAK USIA DINI SEBAGAI DASAR PROGRAM PENGEMBANGAN MOTORIK KASAR DI TK DHARMA WANITA PERSATUAN 1 PAJARAN KECAMATAN PONCOKUSUMO - Evi Nurhidayah; Siti Muntomimah; Mochammad Ramli Akbar (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2025)
This study aims to analyze parents' information needs regarding the importance of early childhood education (PAUD) as the basis for children's gross motor development. One way to improve gross motor skills is through the active involvement of parents in understanding the importance of physical education and programs that suit their children's needs. At Dharma Wanita Persatuan 1 Pajaran Kindergarten, Poncokusumo District, the partnership between parents and the school has not been optimal. Parents' lack of understanding of the role of ECE has resulted in low participation in supporting children's learning activities, including gross motor skills. This study used a qualitative descriptive method with interviews of three parents and two teachers. The results showed that most parents did not understand the importance of physical activity as part of ECE and still relied on information from unofficial media. Therefore, an educational strategy through an effective, collaborative, and sustainable parenting program is needed to increase parents' awareness of the essence of PAUD and its impact on children's overall development, especially gross motor skills. These findings form the basis for the design of appropriate communication and education programs in the PAUD environment.